STEP 1: The Scottish Trauma & Orthopaedics Equality Project: demographics and working patterns of a national workforce - Monu Jabbal; Jennifer Cherry; Deborah Eastwood; Chloe E. H. Scott; Phil Walmsley; Emily Baird (Bone & Joint Open)
Aims: Trauma and Orthopaedic (T&O) surgery has come under scrutiny for lagging behind other medical specialties in promoting gender and cultural equity and diversity within their workforce. The proportions of female, ethnic minority, and sexual and gender minority individuals within orthopaedic membership bodies are disproportionate to the populations they serve. The aim of this study is to report the findings of a national workforce survey of demographics and working patterns within T&O in Scotland. Methods: A questionnaire devised by a working group was delivered by the Client Analyst and Relationship Development (CARD) group. Utilizing a secure third party ensured anonymity for all respondents. Data were recorded and analyzed by the CARD group. Results: A total of 353 responses were recorded, representing 71% of the known workforce. Overall, 261 respondents (74%) identified as male, 85 (24%) female, and seven (2%) preferred not to say. For specialist trainee (ST)3 to ST6, 148 (42%) were female, and for ST7 to ST8, 131 (37%) were female. In total, 226 of all respondents (64%) were white-British, 35 (10%) were white-European, and 92 (26%) were of an ethnic minority background. A total of 321 of respondents (91%) identified as heterosexual, 14 (4%) preferred not to say, and 18 (5%) identified as LGBTQ+ or preferred to self-describe. Conclusion: This is the largest national workforce survey in contemporary surgical literature. The findings demonstrate a greater proportion of female surgeons overall compared to other studies in T&O. This proportion of females was highest among more junior trainees. The Scottish T&O workforce is more ethnically diverse than the demographics of the population it serves. This study suggests that T&O in Scotland is an evolving speciality in terms of equality and diversity, and is making positive progress. Cite this article: Bone Jt Open 2025;6(1):103–108.